2021
DOI: 10.1111/acel.13295
|View full text |Cite
|
Sign up to set email alerts
|

Ageing promotes early T follicular helper cell differentiation by modulating expression of RBPJ

Abstract: Ageing profoundly changes our immune system and is thought to be a driving factor in the morbidity and mortality associated with infectious disease in older people. We have previously shown that the impaired immunity to vaccination that occurs in aged individuals is partly attributed to the effect of age on T follicular helper (Tfh) cell formation. In this study, we examined how age intrinsically affects Tfh cell formation in both mice and humans. We show increased formation of Tfh precursors (pre‐Tfh) but no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 75 publications
1
25
0
Order By: Relevance
“…Therefore, this suggests that a loss of diversity in the T cell repertoire with age does not explain the impaired Tfh differentiation we observed in our study. Impaired Tfh responses to vaccines have been observed in humans and mice ( 9, 45 ), however, interestingly the formation of pre-Tfh cells remains intact but there is a failure to generate bona fide GC Tfh cells ( 45, 46 ). Together with our data, this suggests that instead of intrinsic defects in CD4 + T cells pre-vaccination in older people, the reduced cTfh cell frequency post vaccination may be explained by extrinsic factors, such as inflammation, that lead to a failure to appropriately acquire the GC Tfh cell gene signature.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this suggests that a loss of diversity in the T cell repertoire with age does not explain the impaired Tfh differentiation we observed in our study. Impaired Tfh responses to vaccines have been observed in humans and mice ( 9, 45 ), however, interestingly the formation of pre-Tfh cells remains intact but there is a failure to generate bona fide GC Tfh cells ( 45, 46 ). Together with our data, this suggests that instead of intrinsic defects in CD4 + T cells pre-vaccination in older people, the reduced cTfh cell frequency post vaccination may be explained by extrinsic factors, such as inflammation, that lead to a failure to appropriately acquire the GC Tfh cell gene signature.…”
Section: Discussionmentioning
confidence: 99%
“…Some factors that might account for this discrepancy include different markers used to identify the Tfh cells, different flow cytometric gating strategies, whether Tfr cells are excluded from the Tfh cell population, and whether the studies were looking at antigen-specific Tfh cells or total Tfh cells. Multiple studies have observed that while ageing does not result in defects in the formation of pre-Tfh cells, there is an age-related impairment in their development into mature GC Tfh cells in mice [ 60 , 136 ]. A closer look into the underlying mechanism showed that antigen-specific CD4± Tcells in aged mice post-vaccination have a more regulatory phenotype, characterized by lower IL-2 and increased IL-10 production, and also have lower expression of Tfh cell markers like ICOS and CXCR5, indicating an age-related dysregulation in effector CD4± Tcell differentiation that might contribute to impaired mature Tfh cell formation [ 60 , 137 ].This is also observed for humans, where naïve CD4± Tcells from older donors were observed to have enhanced differentiation into pre-Tfh cells when stimulated via CD3/CD28 without Tfh-polarising cytokines IL-12 and TGFβ, compared to those from younger donors, but older people have impaired antigen-specific cTfh formation post-vaccination [ 73 , 136 ].…”
Section: Mechanisms Underpinning the Age-related Decline Of The Gc Responsementioning
confidence: 99%
“…Age correlates with multiple immunological parameters and also amplifies the degree of variation present, a result of direct effects of age as well as increased environmental exposures over time 1,12 . Age-related immune variation can be due to cumulative effects of immunosenescence, such as lower activity of hematopoietic stem cells 30,31 , altered lineage differentiation 32 , thymic involution 33 , attenuated antiviral responses 34 , leukocyte attrition, or mutation accumulation. Key genetic mutations with increased age include both somatic mutations and mosaic chromosomal alterations (mCAs), such as deletions, duplications, and loss of heterozygosity.…”
Section: Age and Immune Variationmentioning
confidence: 99%